Estimation of surgical blood loss and transfusion requirements in orthopaedic soft tissue tumor surgery: associated factors - Auerkari, Aino Nindya; Tantri, Aida Rosita; Alatas, Anas (DiscoverSys Inc., 2019)
Over half of soft tissue tumor surgeries require intraoperative Packed Red Cell (PRC) transfusion. Transfusion should be sufficient, as inadequacy will increase risk of tissue ischemia, morbidity and mortality. On the other hand, liberal transfusion is related to infection, tumor recurrence, and immunosuppression. Therefore, good PRC planning measures in preoperative period are essential. Several factors that can be identified in the preoperative period, have been associated with surgical bleeding and transfusion in soft tissue tumor surgery. These factors are ASA score, preoperative hemoglobin (Hb) value, malignancy, size, and location of tumor. By acknowledging influencing factors, a system for predicting blood requirement can be established to promote patient safety and avoid waste. This study aimed to determine factors associated with surgical blood loss and intraoperative PRC transfusion.A retrospective cohort was analyzed on 84 records of orthopaedic soft tissue tumor surgery during 2014-2018. In all subjects, the aforementioned factors, amount of intraoperative bleeding and intraoperative PRC transfusion was recorded. Data was analyzed by linear regression to see the relationship of factors to the amount of bleeding and by logistic regression to assess the probability of receiving intraoperative PRC transfusions. A multivariate analysis identified tumor size as an independent determining factor of bleeding. In further analysis, it was found that tumor size and preoperative Hb value were predictors of the probability of requiring intraoperative PRC transfusion.